2016
DOI: 10.1111/jac.12164
|View full text |Cite
|
Sign up to set email alerts
|

Low Incident Light Combined with Partial Waterlogging Impairs Photosynthesis and Imposes a Yield Penalty in Cotton

Abstract: Through field studies, cotton responses to dual stresses -waterlogging and low light (shade) were investigated. The hypothesis was that shade would amplify yield losses in waterlogged (WL) cotton. Either early or late in the reproductive phase, the crop was WL (96 h and 120 h, in 2012-2013 and 2013-2014, respectively) and/or shaded (6 days or 9 days in 2012-2013 and 2013-2014, respectively). Waterlogging at early reproductive phase significantly reduced lint yield (17 % averaged across both years) of cotton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…As most stresses negatively affect cotton growth, the combined effects of two stresses may be more harmful. For instance, the combined effect of waterlogging and heat stress [13], and that of waterlogging and low light were found positively significant [9], which means the combination of two stresses could induce more impairments on cotton than their additive effects. In comparison, our result regarding flood followed by drought stress showed that the combined effect of flood and drought was obviously less than their additive effects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As most stresses negatively affect cotton growth, the combined effects of two stresses may be more harmful. For instance, the combined effect of waterlogging and heat stress [13], and that of waterlogging and low light were found positively significant [9], which means the combination of two stresses could induce more impairments on cotton than their additive effects. In comparison, our result regarding flood followed by drought stress showed that the combined effect of flood and drought was obviously less than their additive effects.…”
Section: Discussionmentioning
confidence: 97%
“…In field conditions, cotton suffers from various factors, such as water deficit, waterlogging, heat stress, shade stress, and limited nutrients [5][6][7][8][9]. The combined stress of two stresses are also common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We A primary interest of this research was to examine how L. melissifolia grown along a gradient of light availability responds to the stress of annual soil flooding. We recognize numerous pathways in which plants may respond to these stress factors (Lenssen et al 2003, Niinemets 2010, Najeeb et al 2016, and these are indicated by the presence or absence of a statistically significant interaction between light availability and soil flooding as they affect plant function. For example, Mielke and Schaffer (2010) found that light availability and soil flooding independently affected biomass accumulation of Eugenia uniflora seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the apparent stress of light deprivation is sufficiently influential on plant function to prevent any further reduction in biomass accumulation due to additional days of soil flooding. Several authors have described this static response by suggesting the impact of one stress factor dominates plant function such that a second stress factor has little or no impact on plant growth (Lenssen et al 2003, Niinemets 2010, Najeeb et al 2016.…”
Section: Mielkementioning
confidence: 99%